High Efficiency Variable-Frequency Full-Bridge Converter with a Load Adaptive Control Method Based on the Loss Model - Lei Zhao (School of Electrical Engineering and Automation, Harbin Institute of Technology, Harbin 150001, China) (MDPI AG, 2018)
In this paper, a load adaptive control method to improve the efficiency and dynamic performance of the Phase-Shifted Full-Bridge (PSFB) converter which works under a wide range of load conditions is presented. The proposed control method can be used as a battery charger since this application demands a wide range of load conditions. The composition of the PSFB converter’s losses and the loss analysis model are both discussed. According to this model, the optimum switching frequency which results in minimum power loss is adopted to improve the efficiency. The relationship between switching frequency and power loss is formulated over a wide load range. Indicated by this kind of relationship, the proposed controller adjusts the switching frequency at different load currents. Moreover, an adaptive gain adjustment controller is applied to replace the traditional controller, with the aim to improve the dynamic performance which is influenced by the changes of the switching frequency and load current. In addition, the experimental results show that the maximum improvement of efficiency is up to 20%. These results confirm the effectiveness of the proposed load adaptive control method.